Geoacoustic Digital Model for the Sea of Japan Shelf (Peter the Great Bay) - Aleksandr Samchenko; Grigory Dolgikh; Igor Yaroshchuk; Roman Korotchenko; Alexandra Kosheleva (Geosciences)
In this paper, the authors present and analyze the geoacoustic digital seabed model they developed, which is a digital description of the water column characteristics, seabed topography, and information about sediments and rocks (their composition and elastic properties) for Peter the Great Bay, the Sea of Japan. The model consists of four relief layers, a foundation and three layers of bottom sediments, and also contains the velocities of longitudinal waves in rocks and statistical characteristics of the sound velocity distribution in the water layer for three seasons. Acoustic characteristics of geological structures are based on seismoacoustic studies, sediment lithology, and laboratory measurements of rock samples collected onshore. The velocities of longitudinal and transversal waves and also the density of the sediments were calculated from their empirical dependencies on the granulometric composition of bottom sediment samples over an area of about 800 km2. In a limited area of the shelf (approximately 130 km2), high-frequency acoustic studies were carried out using echo sounders, and the longitudinal wave velocities of the top sedimentary layer were determined. Porosity, density, longitudinal, and transverse wave velocities in bottom sediments were calculated using empirical models with a normal coefficient of reflection from the seabed. A comparison was made of the results of calculating the elastic properties of the seabed using various methods.